The destruction of Jerusalem in early modern English literature - Garstad, Benjamin (My University, 2017)
Groves’s book examines the recreation, appropriation, and interpretation, in England from after the Reformation to the later seventeenth century, of a signal event in ancient history that loomed large in the early modern imagination. The fall of Jerusalem to the Roman armies of Titus and Vespasian in 70 AD was seen as the conclusion of the Biblical story of the Jews and the fulfillment of the words of no less a prophet than Jesus. The Jewish War of Flavius Josephus, and even the Josippon, the medieval Hebrew translation of parts of the Jewish War, were familiar texts in early modern England. The fall of Jerusalem was not merely a matter of antiquarian interest; it was an occasion for earnest calls to repentance and soul-searching reflections on the state of England. The present book “addresses the way that early modern literature’s response to the fall of Jerusalem was conditioned by, and elucidates, England’s sense of itself” (6). Groves presents the English handling of the fall of Jerusalem as very much a product of the Reformation, a rejection of the triumphalist and anti-Semitic treatment of this same event in medieval and Roman Catholic contexts, which allowed English authors and their audiences to identify with the ancient Jews, similarly assailed by the Romans. Her astute concentration on a few key texts masks a formidable and wide-ranging erudition; her book is not an introduction and demands some familiarity with both Josephus and early modern English literature.
Keywords: Early modern English literature -- History & criticism; Siege of Jerusalem, 70 A.D.; Destruction of Jerusalem in Early Modern English Literature, The (Book); Groves, Beatrice